A história de luta, organização e conquista da Escola Itinerante Chico Mendes – PR - Claudio, Fabiana Gonçalves de Souza (2020)
Recognizing the importance of rescuing and valuing the participation of anonymous subjects in history, this research analyzes the movement carried out by the subjects (educators, students, fathers and mothers), within the scope of the conquest of the Chico Mendes Itinerant School, in the context of the Rural Workers Movement Sem Terra, in the municipality of Quedas do Iguaçu - PR, from 2003 to 2007. To do so, consider the story represented from the bottom up, built from the reality of the Sem Terra subjects, in this case, educators, students, parents and mothers involved in the process of setting up the first approved Itinerant School, legally recognized in the State of Paraná. It is noteworthy that, qualitative research, is defined as a case study, seeking input in bibliographies consistent with the objective of the investigation and in documents prepared by the Landless Rural Workers Movement itself, as well as non-formal records - independent systematizations - in addition to semi-structured interviews with educators, students, fathers and mothers who participated in the process of establishing the Itinerante Chico Mendes School. The study starts from a historical rescue of the struggle for land, with a focus on the struggle of the Landless in the Midwest Region of Paraná, reaching the specificities of the constitution of the José Abílio dos Santos Camp where the Itinerante Chico Mendes School was consolidated. In the context of understanding the historical process of conquest of this school, the second part of the research portrays the constitution of the Itinerant School in the context of the Landless Workers Movement as a counterpoint to the capitalist school, therefore, it addresses considerations of education and the rural school in the context of the Movement. The third, and last, part refers to the contradictions, limits and tensions in the process of organizing the Itinerant School Chico Mendes, in order to highlight not only the limits in the process of constituting the Itinerant School, but the limits imposed on the continuity of the proposal in the context of the Celso Furtado Settlement. In the final considerations, among others, it is concluded that the subjects (educators, students, fathers and mothers), “simple men,” the least favored, can be hidden in the history guided by the insults and perspectives of the dominant classes, they can be devoid of visibility, but not without history, above all, the stories of struggles that, from a distant past, pervade their lives. The decision, which the Movement dared to build a school different from the capitalist school, was in the sense of guaranteeing the right to access school education for the Landless subjects. The School created in the midst of the contradictions, limits and tensions of the process of struggle for land, although neglected by the public authorities, proved to be a possible school, different from the traditional capitalist school, a school created from the struggle of the landless people.